2013
DOI: 10.1007/s13304-013-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy: a single center experience. Unusual cases and expanded inclusion criteria for laparoscopic approach

Abstract: Laparoscopic splenectomy (LS) is nowadays considered as the gold standard for most hematological diseases where splenectomy is necessary, but many questions still remain. The aim of this study was to analyze our 5-years experiences consisting of 48 consecutive LS cases in order to assess the optimal approach and the feasibility of the procedure also in malignant diseases and unusual cases such as a primary spleen lymphoma, a big splenic artery aneurism, or a spleen infarct due to a huge pancreatic pseudo-cyst.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…Most authors prefer the lateral approach for spleen mobilization (7,9,10,14,20). Almost all of them agree that the division of the gastrosplenic ligament and the short gastric vessels can be safely performed using an ultrasonic scalpel, while Al-Mulhim advocates the use of Ligaclips for the ligation of short gastric vessels greater than 4 mm in diameter (7).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most authors prefer the lateral approach for spleen mobilization (7,9,10,14,20). Almost all of them agree that the division of the gastrosplenic ligament and the short gastric vessels can be safely performed using an ultrasonic scalpel, while Al-Mulhim advocates the use of Ligaclips for the ligation of short gastric vessels greater than 4 mm in diameter (7).…”
Section: Resultsmentioning
confidence: 99%
“…A drain tube was routinely placed in all patients. Marte et al suggested that in cases of known or suspected malignancy, the spleen should be retrieved through a Pfannenstiel incision (14). A drain tube was left in all patients for 2 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations